Audiometric Comparison Between the First Patients With the Transcutaneous Bone Conduction Implant and Matched Percutaneous Bone Anchored Hearing Device Users. Issue 9 (October 2016) - Rigato, Cristina; Reinfeldt, Sabine; Håkansson, Bo; Jansson, Karl-Johan Fredén; Hol, Myrthe K. S.; Eeg-Olofsson, Måns
Abstract : Hypothesis: The transcutaneous bone conduction implant (BCI) is compared with bone-anchored hearing aids (BAHAs) under the hypothesis that the BCI can give similar rehabilitation from an audiological as well as patient-related point of view. Background: Patients suffering from conductive and mixed hearing losses can often benefit more from rehabilitation using bone conduction devices (BCDs) rather than conventional air conduction devices. The most widely used BCD is the percutaneous BAHA, with a permanent skin-penetrating abutment. To overcome issues related to percutaneous BCDs, the trend today is to develop transcutaneous devices, with intact skin. The BCI is an active transcutaneous device currently in a clinical trial phase. A potential limitation of active transcutaneous devices is the loss of power in the induction link over the skin. To address this issue, countermeasures are taken in the design of the BCI, which is therefore expected to be as effective as percutaneous BCDs. Methods: An early observational study with a matched-pair design was performed to compare BCI and BAHA groups of patients over several audiometric measurements, including speech audiometry and warble tones thresholds with and without the device. Additionally, questionnaires were used to assess the general health condition, benefit, and satisfaction level of patients. Results: No statistically significant difference was detected in any of the audiological measurements. The outcome of patient-related measurements was slightly superior for BCI in all subscales. Conclusion: Results confirm the initial hypothesis of the study: the BCI seems to be capable of providing as good rehabilitation as percutaneous devices for indicated patients.